Pengujian Slump Beton Alir dengan Penggunaan Serbuk Batu Kapur sebagai pengganti Semen - Napa, Marniantu Helena; Rochmah, Nurul (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
This study aims to analyze the effect of using limestone powder as a partial replacement for cement on the slump value of flowing concrete. The limestone powder substitution was applied in variations of 0%, 5%, 9%, 10%, and 15% of the cement weight to observe changes in the fresh properties of the concrete. The slump test was carried out according to standard methods for flowing concrete to evaluate the workability and flowability of the mixture. The test results showed that the addition of limestone powder with fine particle size was able to increase the slump value because it acts as a filler that improves particle packing and reduces inter-particle friction. However, at substitution levels above the optimum limit, a tendency for segregation began to appear, resulting in reduced mixture stability. Overall, limestone powder can be used as a cement substitute in flowing concrete as long as its percentage is controlled to ensure it still meets the required workability standards.